High-thermal-conductivity aluminum nitride ceramic structural member and preparation method thereof

By using modified aluminum nitride and other additives in aluminum nitride ceramic structural parts and carrying out specific ball milling and sintering processes, the problem of insufficient thermal conductivity and bending strength of existing aluminum nitride ceramic structural parts is solved, and higher thermal conductivity and bending strength are achieved, extending the service life of the equipment and improving the stability of electronic equipment.

CN119797932AActive Publication Date: 2025-04-11MILITARY PORCELAIN ELECTRONIC MATERIALS HEBEI CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510042470.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-11
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

The thermal conductivity and bending strength of existing aluminum nitride ceramic structural parts have insufficient heat, shortened service life and damage to electronic components.

Method used

The thermal conductivity and bending strength of aluminum nitride ceramic structural parts are improved through specific ball milling and sintering processes by using modified aluminum nitride, sintering aids, plasticizers, binders, dispersants and dihydroxyalumina acetate.

Benefits of technology

It significantly improves the thermal conductivity and bending strength of aluminum nitride ceramic structural parts, extends the service life of the equipment, and improves the stability and safety of electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum nitride ceramics, and provides a high-thermal-conductivity aluminum nitride ceramic structural member and a preparation method thereof, the aluminum nitride ceramic structural member comprises the following raw materials by weight: 100 parts of aluminum nitride, 5-10 parts of a sintering aid, 4-6 parts of a plasticizer, 5-10 parts of a binder, 1-1.5 parts of a dispersant, 2-2.5 parts of aluminum dihydroxyamino acetate, and 70-80 parts of a solvent. According to the technical scheme, the problems of low thermal conductivity and low bending strength of the aluminum nitride ceramic structural member in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum nitride ceramics, and in particular to a high thermal conductivity aluminum nitride ceramic structural component and a preparation method thereof. Background Art

[0002] Aluminum nitride ceramic structural parts are ceramic structural parts with aluminum nitride as the main crystal phase, which have important applications in the fields of electronic information, mechanical engineering, chemical industry, optics, etc. In the field of electronic information, aluminum nitride ceramic structural parts mainly include aluminum nitride ceramic substrates and aluminum nitride ceramic shells.

[0003] With the development of high-power and ultra-large-scale integrated circuits, the importance of heat dissipation between integrated circuits and aluminum nitride ceramic substrates has become increasingly apparent. Aluminum nitride ceramic substrates with high thermal conductivity can dissipate heat, prevent equipment from degrading performance and shortening life due to overheating, extend the service life of equipment, and improve the stability of equipment operation. However, the existing aluminum nitride ceramic substrates have the problem of low thermal conductivity; moreover, in electronic packaging, aluminum nitride ceramics are often used as shells for encapsulating electronic components. If the bending strength of the aluminum nitride ceramic shell is low, it is easy to bend and deform or even break when subjected to external force, resulting in damage to the chip, which will also reduce the service life of the electronic equipment.

[0004] Therefore, it is necessary to provide an aluminum nitride ceramic structural component with high thermal conductivity and high bending strength. Summary of the invention

[0005] The present invention provides a high thermal conductivity aluminum nitride ceramic structural component and a preparation method thereof, which solves the problems of low thermal conductivity and low bending strength of the aluminum nitride ceramic structural component in the related art.

[0006] The technical solution of the present invention is as follows: The present invention provides a high thermal conductivity aluminum nitride ceramic structural component, comprising the following raw materials in parts by weight: 100 parts of aluminum nitride, 5 to 10 parts of a sintering aid, 4 to 6 parts of a plasticizer, 5 to 10 parts of a binder, 1 to 1.5 parts of a dispersant, 2 to 2.5 parts of dihydroxyamino aluminum acetate, and 70 to 80 parts of a solvent.

[0007] As a further technical solution, the sintering aid includes one or both of yttrium trioxide and lanthanum oxide.

[0008] As a further technical solution, the sintering aid consists of yttrium trioxide and lanthanum oxide.

[0009] As a further technical solution, the mass ratio of yttrium trioxide to lanthanum oxide is 1:1.

[0010] As a further technical solution, the aluminum nitride is modified aluminum nitride, and the modified aluminum nitride is obtained by modifying aluminum nitride with a modifier, and the modifier includes a surfactant.

[0011] As a further technical solution, the surfactant is nonylphenol polyoxyethylene ether.

[0012] As a further technical solution, the modifier also includes p-acetylaminophenylboronic acid.

[0013] As a further technical solution, the amount of the modifier added is 4% to 6% of the mass of aluminum nitride.

[0014] As a further technical solution, when the modifier is composed of a surfactant and p-acetylaminophenylboronic acid, the mass ratio of the surfactant to the p-acetylaminophenylboronic acid is 3:1-3.

[0015] In the present invention, the thermal conductivity and bending strength of the aluminum nitride ceramic component can be further improved by using a surfactant and para-acetamidophenylboric acid to modify the aluminum nitride.

[0016] As a further technical solution, the preparation method of the modified aluminum nitride comprises the following steps: adding aluminum nitride to water and mixing evenly, adding a modifier for modification, and drying to obtain the modified aluminum nitride.

[0017] As a further technical solution, the modification temperature is 70° C. and the modification time is 3 hours.

[0018] As a further technical solution, the mass volume ratio of the aluminum nitride and water is 1g:10mL.

[0019] As a further technical solution, the plasticizer includes one or both of dibutyl phthalate and diethyl phthalate.

[0020] As a further technical solution, the dispersant includes one or more of sodium pyrophosphate, sodium hexametaphosphate, and triethyl phosphate.

[0021] As a further technical solution, the binder includes one or more of polyvinyl butyral, ethyl cellulose, and polyvinyl alcohol.

[0022] As a further technical solution, the solvent is ethanol.

[0023] The present invention also proposes a method for preparing a high thermal conductivity aluminum nitride ceramic structural component, comprising the following steps: S1, mixing aluminum nitride, a sintering aid, a dispersant, dihydroxyamino aluminum acetate, and a solvent uniformly, and then performing a first ball milling to obtain a mixture; S2, adding a plasticizer and a binder to the mixture, mixing them evenly, and then performing a second ball milling to obtain a casting slurry; S3, tape-casting the tape-casting slurry, drying, and punching to obtain a green body; S4, debinding the green body and sintering it to obtain an aluminum nitride ceramic structural part.

[0024] As a further technical solution, the rotation speeds of the first ball milling and the second ball milling are both 800 rpm, the time of the first ball milling is 3 hours, and the time of the second ball milling is 1 hour.

[0025] As a further technical solution, in step S4, the sintering is to heat the temperature to 1600°C at a heating rate of 5-15°C / min, then heat the temperature to 1700-1900°C at a heating rate of 2-6°C / min, and then sinter for 2-3h.

[0026] As a further technical solution, in step S4, the sintering is to heat the temperature to 1600°C at a heating rate of 10°C / min, then heat the temperature to 1700~1900°C at a heating rate of 5°C / min, and then sinter for 2~3h.

[0027] In the present invention, by limiting the parameter conditions during the sintering process and combining a sintering aid, the thermal conductivity and bending strength of the aluminum nitride ceramic component can be further improved.

[0028] The working principle and beneficial effects of the present invention are: In the present invention, the raw materials of the aluminum nitride ceramic structural member include aluminum nitride, a sintering aid, a plasticizer, a binder, a dispersant, dihydroxyaminoaluminum acetate, etc., wherein aluminum nitride has a high thermal conductivity, the addition of the plasticizer and the binder can increase the flexibility and viscosity of the green body, the addition of the sintering aid can improve the thermal conductivity and bending strength of the aluminum nitride ceramic, and the addition of dihydroxyaminoaluminum acetate can not only improve the thermal conductivity of the aluminum nitride ceramic structural member, but also improve the bending strength of the aluminum nitride ceramic structural member. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In the following examples and comparative examples: the particle size of aluminum nitride is 5 μm; the weight average molecular weight of polyvinyl butyral is 30,000.

[0031] Example 1 A method for preparing a high thermal conductivity aluminum nitride ceramic structural component comprises the following steps: S1, 100 parts of aluminum nitride, 5 parts of sintering aid, 4 parts of dibutyl phthalate, 5 parts of polyvinyl butyral, 1 part of sodium hexametaphosphate, 2 parts of dihydroxyamino aluminum acetate, and 70 parts of ethanol were mixed evenly, and ball-milled at a speed of 800 rpm for 4 hours to obtain a casting slurry; wherein the sintering aid is lanthanum oxide; S2, tape-casting the tape-casting slurry, drying, and punching to obtain a green body; S3. After debinding the green body, the green body is heated to 1600° C. at a heating rate of 5° C. / min in a nitrogen atmosphere, and then heated to 1700° C. at a heating rate of 2° C. / min, and then sintered for 3 hours to obtain an aluminum nitride ceramic structural part.

[0032] Example 2 A method for preparing a high thermal conductivity aluminum nitride ceramic structural component comprises the following steps: S1, 100 parts of aluminum nitride, 10 parts of sintering aid, 6 parts of diethyl phthalate, 10 parts of polyvinyl butyral, 1.5 parts of triethyl phosphate, 2.5 parts of dihydroxyamino aluminum acetate, and 80 parts of ethanol were mixed evenly, and ball-milled at a speed of 800 rpm for 4 hours to obtain a casting slurry; wherein the sintering aid is lanthanum oxide; S2, tape-casting the tape-casting slurry, drying, and punching to obtain a green body; S3. After debinding the green body, the green body is heated to 1600° C. at a heating rate of 15° C. / min in a nitrogen atmosphere, and then heated to 1900° C. at a heating rate of 6° C. / min, and then sintered for 2 hours to obtain an aluminum nitride ceramic structural part.

[0033] Example 3 A method for preparing a high thermal conductivity aluminum nitride ceramic structural component comprises the following steps: S1, after uniformly mixing 100 parts of aluminum nitride, 5 parts of a sintering aid, 1 part of sodium hexametaphosphate, 2 parts of dihydroxyamino aluminum acetate, and 70 parts of ethanol, ball milling was performed at a rotation speed of 800 rpm for 3 hours to obtain a mixture; wherein the sintering aid is lanthanum oxide; S2, adding 4 parts of dibutyl phthalate and 5 parts of polyvinyl butyral to the mixture, and ball milling at a rotation speed of 800 rpm for 1 hour to obtain a casting slurry; S3, tape-casting the tape-casting slurry, drying, and punching to obtain a green body; S4. After debinding the green body, the green body is heated to 1600° C. at a heating rate of 5° C. / min in a nitrogen atmosphere, and then heated to 1700° C. at a heating rate of 2° C. / min, and then sintered for 3 hours to obtain an aluminum nitride ceramic structural part.

[0034] Example 4 Compared with Example 3, the only difference of this embodiment is that the aluminum nitride is modified aluminum nitride. The preparation method of the modified aluminum nitride in this embodiment is as follows: after adding aluminum nitride to water and mixing evenly, adding nonylphenol polyoxyethylene ether, stirring at 70°C for 3h, and drying to obtain modified aluminum nitride; wherein the mass volume ratio of aluminum nitride to water is 1g:10mL, and the amount of nonylphenol polyoxyethylene ether added is 6% of the mass of aluminum nitride.

[0035] Example 5 Compared with Example 4, the only difference of this example is that nonylphenol polyoxyethylene ether is replaced by an equal amount of para-acetamidophenylboric acid.

[0036] Example 6 Compared with Example 4, the only difference of this example is that nonylphenol polyoxyethylene ether is replaced by equal amounts of nonylphenol polyoxyethylene ether and para-acetamidophenylboric acid in a mass ratio of 3:1.

[0037] Example 7 Compared with Example 6, the only difference in this example is that the mass ratio of nonylphenol polyoxyethylene ether to 4-acetamidophenylboric acid is 3:2.

[0038] Example 8 Compared with Example 6, the only difference in this example is that the mass ratio of nonylphenol polyoxyethylene ether to 4-acetamidophenylboric acid is 1:1.

[0039] Example 9 Compared with Example 7, the only difference of this example is that the total mass of nonylphenol polyoxyethylene ether and 4-acetamidophenylboric acid added is 4% of the mass of aluminum nitride.

[0040] Example 10 Compared with Example 7, the difference of this embodiment is only in step S4. Step S4 of this embodiment is: S4, after debinding the green body, heat it to 1600°C at a heating rate of 15°C / min in a nitrogen atmosphere, and then heat it to 1700°C at a heating rate of 2°C / min, and sinter it for 3 hours to obtain an aluminum nitride ceramic structural part.

[0041] Embodiment 11 Compared with Example 7, the difference of this embodiment is only in step S4. Step S4 of this embodiment is: S4, after debinding the green body, heat it to 1600°C at a heating rate of 10°C / min in a nitrogen atmosphere, and then heat it to 1700°C at a heating rate of 2°C / min, and sinter it for 3 hours to obtain an aluminum nitride ceramic structural part.

[0042] Example 12 Compared with Example 7, the difference of this embodiment is only in step S4. Step S4 of this embodiment is: S4, after debinding the green body, heat it to 1600°C at a heating rate of 10°C / min in a nitrogen atmosphere, and then heat it to 1700°C at a heating rate of 8°C / min, and sinter it for 3 hours to obtain an aluminum nitride ceramic structural part.

[0043] Embodiment 13 Compared with Example 11, the only difference of this example is that the sintering aid consists of yttrium trioxide and lanthanum oxide in a mass ratio of 1:1.

[0044] Comparative Example 1 Compared with Example 1, the difference of this comparative example is only that no dihydroxyaminoacetic acid aluminum is added.

[0045] The flexural strength and thermal conductivity of the aluminum nitride ceramic structural member samples prepared in Examples 1 to 13 and Comparative Example 1 were respectively measured. The flexural strength of the samples was measured according to the three-point bending test of GB / T 6569-2006 "Test method for flexural strength of fine ceramics"; the thermal conductivity of the samples was measured according to GB / T 32064-2015 "Test method for thermal conductivity and thermal diffusivity of building materials by transient plane heat source", and the measurement results are shown in Table 1.

[0046] Table 1 Performance measurement results of aluminum nitride ceramic structural parts in Examples 1 to 13 and Comparative Example 1

[0047] Compared with Comparative Example 1, dihydroxyaminoaluminum acetate was added in Example 1. As a result, the thermal conductivity and bending strength of the aluminum nitride ceramic structural component in Example 1 were higher than those in Comparative Example 1, indicating that the addition of dihydroxyaminoaluminum acetate can improve the thermal conductivity and bending strength of the aluminum nitride ceramic structural component.

[0048] Compared with Example 1, the raw materials in Example 3 were ground twice. As a result, the thermal conductivity and bending strength of the aluminum nitride ceramic structural parts in Example 3 were higher than those in Example 1, indicating that grinding the raw materials twice can improve the thermal conductivity and bending strength of the aluminum nitride ceramic structural parts.

[0049] Compared with Example 3, Examples 4 to 8 use different modifiers to modify aluminum nitride. As a result, the thermal conductivity and bending strength of the aluminum nitride ceramic structural parts in Examples 6 to 8 are higher than those in Examples 3 to 5, indicating that the thermal conductivity and bending strength of the aluminum nitride ceramic structural parts can be further improved by modifying aluminum nitride with nonylphenol polyoxyethylene ether and para-acetamidophenylboric acid.

[0050] Compared with Example 6, Examples 7 to 8 change the ratio of nonylphenol polyoxyethylene ether to 4-acetaminophenylboric acid. As a result, the thermal conductivity and bending strength of the aluminum nitride ceramic component in Example 7 are higher than those in Example 6 and Example 8, indicating that when the mass ratio of nonylphenol polyoxyethylene ether to 4-acetaminophenylboric acid is 3:2, the thermal conductivity and bending strength of the aluminum nitride ceramic structural component can be further improved.

[0051] Compared with Example 7, Examples 10 to 12 change the sintering conditions, and Example 13 changes the sintering aid. As a result, the thermal conductivity and bending strength of the aluminum nitride ceramic component in Example 11 are higher than those in Examples 10 and 12. At the same time, the thermal conductivity and bending strength of the aluminum nitride ceramic component in Example 13 are higher than those in Example 11, indicating that the limitation of the sintering aid and sintering conditions in the present invention can further improve the thermal conductivity and bending strength of the aluminum nitride ceramic component.

[0052] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high thermal conductivity aluminum nitride ceramic structural component, characterized in that: The raw materials include the following components in parts by weight: 100 parts of aluminum nitride, 5 to 10 parts of sintering aid, 4 to 6 parts of plasticizer, 5 to 10 parts of binder, 1 to 1.5 parts of dispersant, 2 to 2.5 parts of dihydroxyamino aluminum acetate, and 70 to 80 parts of solvent.

2. The high thermal conductivity aluminum nitride ceramic structural component according to claim 1, characterized in that: The sintering aid includes one or both of yttrium trioxide and lanthanum oxide.

3. The high thermal conductivity aluminum nitride ceramic structural component according to claim 1, characterized in that: The aluminum nitride is modified aluminum nitride, and the modified aluminum nitride is obtained by modifying aluminum nitride with a modifier, and the modifier includes a surfactant.

4. The high thermal conductivity aluminum nitride ceramic structural component according to claim 3, characterized in that: The modifying agent also includes p-acetylaminophenylboronic acid.

5. The high thermal conductivity aluminum nitride ceramic structural component according to claim 3, characterized in that: The amount of the modifier added is 4% to 6% of the mass of aluminum nitride.

6. The high thermal conductivity aluminum nitride ceramic structural component according to claim 3, characterized in that: When the modifier consists of a surfactant and p-acetylaminophenylboronic acid, the mass ratio of the surfactant to the p-acetylaminophenylboronic acid is 3:1-3.

7. The high thermal conductivity aluminum nitride ceramic structural component according to claim 1, characterized in that: The plasticizer includes one or both of dibutyl phthalate and diethyl phthalate.

8. The high thermal conductivity aluminum nitride ceramic structural component according to claim 1, characterized in that: The dispersant includes one or more of sodium pyrophosphate, sodium hexametaphosphate, and triethyl phosphate.

9. The method for preparing a high thermal conductivity aluminum nitride ceramic structural component according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, mixing aluminum nitride, a sintering aid, a dispersant, dihydroxyamino aluminum acetate, and a solvent uniformly, and then performing a first ball milling to obtain a mixture; S2, adding a plasticizer and a binder to the mixture, mixing them evenly, and then performing a second ball milling to obtain a casting slurry; S3, tape-casting the tape-casting slurry, drying, and punching to obtain a green body; S4, debinding the green body and sintering it to obtain an aluminum nitride ceramic structural part.

10. The method for preparing a high thermal conductivity aluminum nitride ceramic structural component according to claim 9, characterized in that: In step S4, the sintering is to heat the temperature to 1600° C. at a heating rate of 5 to 15° C. / min, then heat the temperature to 1700 to 1900° C. at a heating rate of 2 to 6° C. / min, and then sinter for 2 to 3 hours.

Citation Information

Patent Citations

  • Method for preparing bionic ecological building material by treating beach silt

    CN108545995A

  • Low-temperature rise magnetic core and preparation method thereof

    CN109534808A

  • Photocuring aluminum nitride ceramic slurry and preparation method of aluminum nitride ceramic

    CN109761615A

  • Aluminum nitride ceramic substrate and preparation method thereof

    CN118637924A

  • Corrosion-resistant aluminum nitride ceramic substrate and preparation method thereof

    CN118684501A